Loss Aversion and An Equity Risk Premium in The Emerging Markets - Kushnir, Myroslava; Кушнір, Мирослава (Black Sea Scientific Journal Of Academic Research., 2015)
In the paper it was provided an explanation to the equity risk premium in emerging and developed markets. The research was based on the Capital asset pricing model under Prospect theory. The model presented the relationship between the loss aversion degree and the equilibrium market price of risk. We applied the model in an empirical data of developed and emerging markets in two different periods. It was found that the emerging markets have higher loss aversion in the research period. This fact was the reason of the higher equity risk premium in these markets. The loss aversion level of the market depends also on the time period.
Keywords: Prospect theory; loss aversion; equity risk premium